Prospects of small-scale rice processing enterprise among beneficiaries of microfinance loan in Nigeria’s Jigawa State - sadiq, sanusi (Revista Economía, 2024)
The present study empirically determined the prospects of rice value chain of paddy processors in Jigawa State of Nigeria. In spite of the role of small-scale paddy rice processors as the main engine of growth of upstream rice value chain; growth and development of rural economy in the study area, literature is undaunted with paucity of empirical information on the prospects of rice processing value chain in the study area. The study utilized cross-sectional data elicited through a well-structured questionnaire from a total of 200 processors (133 par-boilers and 67 millers) selected through a multi-stage sampling technique. An easy cost-route approach was used for data collection during the 2022 processing period and the collected data were analyzed using both descriptive and inferential statistics. Based on the empirical evidence, it is established that rice processing potential has not been fully exploited in the study area. In addition, it is evident that rice processing enterprise not only being viable and profitable; it holds a good prospect in the supply value chain of rice in the study area. However, for the prospects in the supply value chain to hold well, the target actors must adopt a defensive mechanism as inferred by the space matrix.